The Effects of Race and Gender When Predicting Intimate Partner Violence Recidivism in Police Reports Using the Ontario Domestic Assault Risk Assessment - Hilton, N. Zoe (Crime & delinquency, 2024)
Despite a growth in risk assessment for intimate partner violence (IPV), validation research has focused on men’s violence against women leading to a dearth of research among other genders and racialized populations. We examined validity of an IPV risk assessment tool in 448 Black and White men and women identified as IPV perpetrators by a United States urban police service. The Ontario Domestic Assault Risk Assessment (ODARA) predicted new police reports of IPV in a fixed 2-year follow up (baserate = 33%, AUC = 0.59). Predictive effects were mostly small, with few significant differences between groups. Further research should examine the benefits and potential harms of IPV risk assessment to individuals who identify within minority race and gender groups.